The microglial P2Y 6 receptor mediates neuronal loss and memory deficits in neurodegeneration - Puigdellívol, Mar; Milde, Stefan; Vilalta, Anna; Cockram, Tom O J; Allendorf, David H; Lee, Jeffrey Y; Dundee, Jacob M; Pampuščenko, Katryna; Borutaite, Vilmante; Nuthall, Hugh N; Brelstaff, Jack H; Spillantini, Maria Grazia; et al. (Cell reports (Cambridge), 2021)
Microglia are implicated in neurodegeneration, potentially by phagocytosing neurons, but it is unclear how to block the detrimental effects of microglia while preserving their beneficial roles. The microglial P2Y receptor (P2Y R) - activated by extracellular UDP released by stressed neurons - is required for microglial phagocytosis of neurons. We show here that injection of amyloid beta (Aβ) into mouse brain induces microglial phagocytosis of neurons, followed by neuronal and memory loss, and this is all prevented by knockout of P2Y R. In a chronic tau model of neurodegeneration (P301S TAU mice), P2Y R knockout prevented TAU-induced neuronal and memory loss. In vitro, P2Y R knockout blocked microglial phagocytosis of live but not dead targets and reduced tau-, Aβ-, and UDP-induced neuronal loss in glial-neuronal cultures. Thus, the P2Y receptor appears to mediate Aβ- and tau-induced neuronal and memory loss via microglial phagocytosis of neurons, suggesting that blocking this receptor may be beneficial in the treatment of neurodegenerative diseases.